The atmospheric gaze as a guiding principle in destination development - Volgger, Michael (2022)
It is well-known that tourists are not primarily attracted by products or services, but they choose and recall destinations based on experiences. A critical though neglected aspect of tourist experiences are atmospheres, which can be conceived as the diffuse and difficult to grasp holistic entities that consist of a combination of spaces and feelings. Based on an interdisciplinary exploration of traditions of atmospheric theorising, this paper aims to delineate and motivate an “atmospheric gaze” as a guiding principle in destination development. With its recognition of genius loci, that is the quasi-objective spirit of a place, the atmospheric gaze is sensitive to the affective characteristics of places and understands them as unique assets in tourism development as well as regional development. This paper argues that the focus on emotional, symbolic, and interactive aspects of places, which is inherent to the atmospheric gaze, can help to achieve a more long-term orientated and balanced destination development.